(untitled) (Fiep Bulletin - online, 2014)
Through experiences of dance with elderly, where there were many difficulties and doubts about the didactic - methodological resources to be used, emerged the interest for this study, which aims to identify and analyze the didactic - methodological processes used for dance in elderly groups teaching in the city of Santa Maria/RS. This research is justified by our belief that from the analysis and reflection on the didactic - methodological process, we can contribute to the pedagogic practice of the teachers who work dance to elderly, and that this study intends to point some suggestions to the most adequate methodology for this population. The study is characterized as descriptive, the subjects are the physical education teachers that work dance to elderly in this city; as research instruments we used the (direct) observation of the classes and the interview (semi structured) with the teachers. We hope to reach our goal, contributing for the pedagogic practice in a way the teachers obtain some reference about the didactic - methodological processes used for the elderly groups, and changing dance into something more then a simple practice, in something that passes through body and becomes part of history and life of the learners.